2019
DOI: 10.22312/sdusbed.490651
|View full text |Cite
|
Sign up to set email alerts
|

Son Trimesterdeki Gebelerin Uyku Kalitelerinin ve Uyku Problemlerine Karşı Başetme Yöntemlerinin Belirlenmesi

Abstract: Uyku fizyolojik bir gereksinim olmakla birlikte yaşam kalitesini ve sağlığı etkileyen temel faktörlerden biridir. Bebeğin hareketleri, sık idrara çıkma, mide yanması gibi şikâyetlerin görüldüğü gebeliğin son 3 ayında uyku kalitesi etkilenmektedir. Çalışmamızın amacı araştırma kapsamındaki gebelerin uyku kalitelerini belirlemektir. Materyal-Metot: Amasya Üniversitesi Sabuncuoğlu Şerefeddin Eğitim Araştırma Hastanesi kadın hastalıkları ve doğum polikliniğine başvuran ve gebeliğinin son 3 ayındaki gebeleri kapsay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…In another study conducted with Chinese pregnant women, it was determined that pregnancy-specific stress was a risk factor for poor sleep quality and endurance was reported as a protective factor (12). In a study conducted in Turkey, it was emphasized that sleep quality was poor in last trimester pregnant women and that the coping methods of pregnant women were inadequate (21). In this direction, it was evaluated that there is a need to develop evidence-based intervention strategies to reduce stress and improve sleep quality in addition to evaluating only stress and sleep quality of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study conducted with Chinese pregnant women, it was determined that pregnancy-specific stress was a risk factor for poor sleep quality and endurance was reported as a protective factor (12). In a study conducted in Turkey, it was emphasized that sleep quality was poor in last trimester pregnant women and that the coping methods of pregnant women were inadequate (21). In this direction, it was evaluated that there is a need to develop evidence-based intervention strategies to reduce stress and improve sleep quality in addition to evaluating only stress and sleep quality of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Poor sleep quality during pregnancy is associated with adverse maternal, fetal and neonatal outcomes such as preterm delivery, prolonged labor, increased caesarean section rates, preeclampsia, postpartum depression, intrauterine growth retardation, and neonatal infections (16,(18)(19)(20). Good sleep quality is essential for a healthy pregnancy (21).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, women in the third trimester experienced significantly more problems regarding sleep latency, sleep quality and sleep (Yeral 2019). Many other studies also showed a decrease in total sleep time, daytime sleepiness, disrupted night sleep and increased frequency of sleeplessness in the third trimester (Çelik and Köse 2017, Köybası and Oskay 2017, Özorhan et al 2014, Öztürk et al 2019. Çoban and Yanıkkerem (2010) found a negative relation between gestational week and sleep quality and noted that as the gestational week increased, the sleep quality decreased (Çoban and Yanıkkerem 2010).…”
Section: Introductionmentioning
confidence: 92%
“…Hemşireler, gebe kadınların uykusunu değerlendirirken son 1 aydaki uyku kalitesini açığa çıkartan Pıttsburgh Uyku Kalitesi İndeksi, uyku apne riski için Berlin Uyku Anketi ve gündüz uykululuğunu değerlendirmek için Epworth Uykululuk Skalası gibi araçları kullanabilir (31,47,48,49). Hemşirelerin, gebelerin uyku kalitesini etkileyen faktörleri belirlemeleri ve etkene yönelik çözüm üretmeleri konusunda teşvik etmeleri önemli olacaktır (50).…”
Section: Gebelikte Uyku Sorunlarının çöZümünde Hemşirelik Yaklaşımıunclassified